2007
DOI: 10.1097/wnr.0b013e3282f0d40c
|View full text |Cite
|
Sign up to set email alerts
|

Development and organization of the human brain tissue compartments across the lifespan using diffusion tensor imaging

Abstract: We used a diffusion tensor imaging-based whole-brain tissue segmentation to characterize age-related changes in (a) whole-brain grey matter, white matter, and cerebrospinal fluid relative to intracranial volume and (b) the corresponding brain tissue microstructure using measures of diffusion tensor anisotropy and mean diffusivity. The sample, a healthy cohort of 119 right-handed males and females aged 7-68 years. Our results demonstrate that white matter and grey matter volumes and their corresponding diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
87
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 17 publications
18
87
0
Order By: Relevance
“…WM FA tends to decrease with aging in men and women (reviewed in Moseley 2002). Similar to the volumetric data, FA peaks in early middle age when myelination peaks (Kemper 1994) and then declines in the elderly at a rate that parallels or precedes WM volumetric loss (Hasan et al 2007;Hasan et al 2008;Hasan et al 2010;Lebel et al 2010;Westlye et al 2010). Regionally, age-related deficits of FA have been described in the genu of the CC centrum semiovale, frontal, and parietal pericallosal WM of men (Pfefferbaum et al 2000), with a similar pattern found in both sexes (Sullivan et al 2001).…”
Section: Diffusion Tensor Imaging In Humansmentioning
confidence: 77%
“…WM FA tends to decrease with aging in men and women (reviewed in Moseley 2002). Similar to the volumetric data, FA peaks in early middle age when myelination peaks (Kemper 1994) and then declines in the elderly at a rate that parallels or precedes WM volumetric loss (Hasan et al 2007;Hasan et al 2008;Hasan et al 2010;Lebel et al 2010;Westlye et al 2010). Regionally, age-related deficits of FA have been described in the genu of the CC centrum semiovale, frontal, and parietal pericallosal WM of men (Pfefferbaum et al 2000), with a similar pattern found in both sexes (Sullivan et al 2001).…”
Section: Diffusion Tensor Imaging In Humansmentioning
confidence: 77%
“…For example, Anokhin et al (1996) and MeyerLindenberg (1996) demonstrated that while EEG power shows a progressive decrease as a function of age, correlation dimension values increase linearly within the age interval of 7 to 60 years. Similarly, while neuroanatomical studies on GM development show a progressive reduction of its volume which starts in childhood (Giedd et al 1999;Sowell et al 1999;Steen et al 1997), WM investigations tend to exhibit an opposite tendency (Ben Bashat et al 2005;Gao et al 2009;Hasan et al 2009;Hasan et al 2007). These parallel trajectories of WM and complexity values might appear as apparently broken during late adulthood, since some studies (see for example McLaughlin et al 2007) demonstrated a FA peak in young adulthood followed by a decline.…”
Section: Discussionmentioning
confidence: 97%
“…Given previous reports (Allen et Rauch and Jinkins, 1994), both linear and quadratic age terms were included. The DTI metrics (e.g., FA,λ ⊥ ) were modeled (fitted) for both males and females as y f =β 0 +β 1 *age+β 2 *age 2 , then the general least-squares methods were used to compute the coefficients, standard errors and their significance using analysis-of-variance (ANOVA) methods (Hasan et al, 2007b;Hasan et al, 2008). For comparison of two fit parameters between males and females, we used a two-tailed t-test of the difference (β iM -β iF ) divided by the root of the pooled variance σ(β iM ) 2 +σ(β iF ) 2 at the corresponding degrees of freedom (Glantz, 2002).…”
Section: Discussionmentioning
confidence: 99%